Associations of environmental pollution with pro-oxidant, antioxidant and inflammatory markers in pregnant mothers and newborns - Ambroz, Antonin; Klema, Jiri; Rossnerova, Andrea; Milcova, Alena; Pastorkova, Anna; Pulkrabova, Jana; Parizek, Ondrej; Gomersall, Veronika; Gramblicka, Tomas; Zelenka, Jaroslav; Ruml, Tomas; Vrzackova, Nikola; et al. (Frontiers in Toxicology, 2025)
The aim of the study was to analyze the variables that modify the levels of oxidative DNA damage and lipid peroxidation in non-smoking mothers and their newborns from environmentally distinct localities of the Czech Republic: Ceske Budejovice (CB, an agricultural region) and Karvina (an industrial region). Personal, socio-economic and medical data, concentrations of particulate matter of aerodynamic diameter < 2.5 µm (PM2.5) and benzo[a]pyrene (B[a]P) in the ambient air, the activities of antioxidant mechanisms (superoxide dismutase, catalase, glutathione peroxidase) and antioxidant capacity), the levels of pro-inflammatory cytokines, the concentrations of persistent organic pollutants (POPs) in blood plasma/cord blood plasma and urinary levels of polycyclic aromatic hydrocarbons metabolites (OH-PAHs) were investigated as parameters potentially affecting the markers of DNA oxidation (8-oxo-7,8-dihydro-2′-deoxyguanosine, 8-oxodG) and lipid peroxidation (15-F2t-isoprostane, 15-F2t-IsoP). Significantly higher levels of POPs were detected in the plasma of mothers/newborns from CB (p < 0.001), while increased external levels of B[a]P and PM2.5, confirmed by analyzing urinary OH-PAHs, were found in Karvina subjects (p < 0.001). In mothers, multivariate analysis showed no significant difference in oxidative stress markers (15-F2t-IsoP, 8-oxodG) between the two localities. The analysis further revealed that neither in CB nor, unexpectedly, in Karvina, did PAH exposure affect maternal lipid peroxidation. Significant associations between OH-PAHs and 15-F2t-IsoP or 8-oxodG were observed only in newborns. In addition, multivariate analyses revealed a borderline significant association between locality and 8-oxodG in the urine of all newborns (p = 0.05). In conclusion, not only the maternal exposure of PAHs but also some POPs can negatively affect oxidative stress status in the early-life of newborns.